Chikungunya Outbreak, South India, 2006 - Prabhdeep Kaur; Manickam Ponniah; Manoj V. Murhekar; Vidya Ramachandran; Ramakrishnan Ramachandran; Hari Kishan Raju; Vanamail Perumal; Akhilesh C. Mishra; Mohan D. Gupte (Emerging Infectious Diseases, 2008)
We investigated chikungunya outbreaks in South India and observed a high attack rate, particularly among adults and women. Transmission was facilitated by Aedes aegypti mosquitoes in peridomestic water containers, as indicated by a high Breteau index. We recommended vector control measures and health education to promote safe water storage practices.